2018
DOI: 10.1038/s41598-018-28764-5
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila microbiome has a limited influence on sleep, activity, and courtship behaviors

Abstract: In animals, commensal microbes modulate various physiological functions, including behavior. While microbiota exposure is required for normal behavior in mammals, it is not known how widely this dependency is present in other animal species. We proposed the hypothesis that the microbiome has a major influence on the behavior of the vinegar fly (Drosophila melanogaster), a major invertebrate model organism. Several assays were used to test the contribution of the microbiome on some well-characterized behaviors:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
44
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 59 publications
7
44
1
Order By: Relevance
“…Of note, many recent studies focus on the influence of commensal bacteria on adult fly behavior, such as locomotion [9,10], feeding [11,12], social interactions [10,13] and egg-laying [14]. These are important advances but will not be covered in this review.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, many recent studies focus on the influence of commensal bacteria on adult fly behavior, such as locomotion [9,10], feeding [11,12], social interactions [10,13] and egg-laying [14]. These are important advances but will not be covered in this review.…”
Section: Introductionmentioning
confidence: 99%
“…However, further work is needed to identify the exact neurons and neuronal mechanisms involved, including potential changes in firing patterns. It would also be important to clarify the sex-specific aspects of these microbial effects on locomotion 30,46 . It is intriguing that germ-free mice display hyperactivity similar to axenic Drosophila , and specific bacteria have been shown to decrease locomotor activity in mice 1,47,48 , although the neuronal pathways implicated in mammalian systems have yet to be identified.…”
mentioning
confidence: 99%
“…Microbiota also appear to interact with insulin signalling which is known to regulate feeding and sleep (Shin et al, 2011). While microbiome composition has been shown to affect mating choice (Sharon et al, 2010), egg laying, and feeding (Leitao-Goncalves et al, 2017), rather surprisingly, another study found that eliminating the microbiome in fruit flies has only very modest effects on sleep and locomotion compared to controls (Selkrig et al, 2018). Considering the wealth of literature describing the interconnection between the availability and quality of food on sleep, it is surprising that loss of gut microbiota has no effect on sleep (Selkrig et al, 2018).…”
Section: Feeding and Sleep Are Mutually Exclusive Behavioursmentioning
confidence: 99%
“…While microbiome composition has been shown to affect mating choice (Sharon et al, 2010), egg laying, and feeding (Leitao-Goncalves et al, 2017), rather surprisingly, another study found that eliminating the microbiome in fruit flies has only very modest effects on sleep and locomotion compared to controls (Selkrig et al, 2018). Considering the wealth of literature describing the interconnection between the availability and quality of food on sleep, it is surprising that loss of gut microbiota has no effect on sleep (Selkrig et al, 2018). While admittedly we cannot definitive rule out whether microbiota composition has an effect on sleep; for now we can say with a degree of confidence that food-induced changes in sleep is mostly governed by taste and nutritional quality.…”
Section: Feeding and Sleep Are Mutually Exclusive Behavioursmentioning
confidence: 99%